Design of a mobile app for crisis guidance - Kiiveri, Kimmo; Liesivuori, Jyrki; Virtanen, Seppo; Isoaho, Jouni (Netherlands, 2025)
This study examines the use of an Online Application Generator (OAG) for low code mobile app design and development, focusing on transforming crisis management guidance from PDF format to a published platform-independent mobile app. We compare the level of difficulty experienced by a citizen developer and a full-stack developer, considering ease of development, customization, security, and architecture. Despite OAGs’ effectiveness in managing vulnerabilities, they pose risks such as undisclosed tracking and compliance with privacy laws. The approach was found feasible for citizen developers in terms of rapid mobile app development although we observed limitations in localization and in preserving privacy.
The 15th International Conference on Ambient Systems, Networks and Technologies Networks (ANT) / The 7th International Conference on Emerging Data and Industry 4.0 (EDI40), April 23-25, 2024, Hasselt University, Belgium